Workplace bullying in nursing: The case of Azerbaijan province, Iran - Esfahani, Ali Nasr (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Workplace bullying is a significant issue confronting the nursing profession both in Iran and internationally. This study examined workplace bullying among a group of Iranian nurses. MATERIALS AND METHODS: The prevalence rate of bullying behavior among nurses was determined. Data were collected from 162 nurses who worked in four hospitals located in West Azerbaijan province, Iran. RESULTS: Results showed that only 9% of nurses who participated in this study had frequently been exposed to bullying behavior, 22% had occasionally been bullied, and 69% had never been exposed to these behaviors during the last year. The most common type of workplace bullying experienced by nurses was verbal bullying. Forty percent of the nurses reported exposure to verbal bullying behavior frequently or occasionally. CONCLUSIONS: To be able to intervene with bullying behavior in the workplace, there is a need to pay greater attention to the problem by the entire range of managers, lawyers, industrial–organizational psychologists, counselors, social workers, and local authorities.